2009
DOI: 10.1371/journal.pntd.0000493
|View full text |Cite
|
Sign up to set email alerts
|

Dengue 1 Diversity and Microevolution, French Polynesia 2001–2006: Connection with Epidemiology and Clinics

Abstract: BackgroundDengue fever (DF) is an emerging infectious disease in the tropics and subtropics. Determinants of DF epidemiology and factors involved in severe cases—dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS)—remain imperfectly characterized. Since 2000, serotype 1 (DENV-1) has predominated in the South Pacific. The aim of this study was (i) to determine the origin and (ii) to study the evolutionary relationships of DENV-1 viruses that have circulated in French Polynesia (FP) from the severe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 35 publications
4
55
3
3
Order By: Relevance
“…In contrast, elimination of deleterious mutations (purifying selection) strongly limits in situ evolution of lineages (23). Purifying selection is likely the dominant evolutionary force in DENV evolution (20), and nucleotide fixation events are due primarily to genetic drift (13,20,26). Although stochastic processes are undoubtedly important in DENV evolution, the present study indicates that more dramatic major clade replacement events may have an adaptive basis (43).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, elimination of deleterious mutations (purifying selection) strongly limits in situ evolution of lineages (23). Purifying selection is likely the dominant evolutionary force in DENV evolution (20), and nucleotide fixation events are due primarily to genetic drift (13,20,26). Although stochastic processes are undoubtedly important in DENV evolution, the present study indicates that more dramatic major clade replacement events may have an adaptive basis (43).…”
Section: Discussionmentioning
confidence: 81%
“…This lineage turnover is detected in phylogenetic analyses in two different, nonmutually exclusive forms: (i) continuous, ladderlike temporal structure within clades and (ii) more dramatic, major clade replacement events. Within a clade, the majority of sublineages present at a specific time point are not detected at later time points, resulting in a ladderlike tree topology (8,13,26). Occasionally, an entire clade that persisted for a number of years at a given location goes extinct as an entirely new clade takes over.…”
mentioning
confidence: 99%
“…Several previous studies have confirmed that the population of DENV in humans and within individual Aedes mosquitoes contains measurable genetic variation (8,19,33,34). Levels of withinhost genetic diversity have been previously shown to vary among patients.…”
mentioning
confidence: 78%
“…The basis for the genetic diversity in DENV is its error-prone RNA polymerase (10), such that mutations commonly occur during viral replication and on which a combination of genetic drift and negative and/or positive natural selection is able to act. This high rate of replication error results in DENV existing as a population of closely related variants within an individually infected host (33, 34), and this intrahost genetic diversity has been proposed to have implications for pathogenesis of DENV infection, variable disease outcomes, virus evolution, and host immunity (6).Several previous studies have confirmed that the population of DENV in humans and within individual Aedes mosquitoes contains measurable genetic variation (8,19,33,34). Levels of withinhost genetic diversity have been previously shown to vary among patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation